o filter : the inside story of Instagram - Frier, Sarah (London Random House Business, 2020)
"Award-winning reporter Sarah Frier reveals an inside, never-before-told, behind-the-scenes look at how Instagram defied the odds to become one of the most culturally defining apps of the decade"--
Keywords: Online social networks; Photography -- Digital techniques